Análise do teletrabalho dos servidores da Universidade Federal de Minas Gerais nos anos de pandemia de covid-19 - 2020 e 2021 com foco na extensão universitária - Gilma Pereira de Oliveira (2024)
Teleworking took place at UFMG during the covid-19 pandemic. Due to this context, the following question arises: what were the impacts caused by teleworking in 2020 and 2021 at the Federal University of Minas Gerais? This study investigates the impacts of teleworking on the staff of the Dean of Extension (Proex) and on the performance of extension activities at the Federal University of Minas Gerais in 2020-2021, amidst the covid-19 pandemic. We also investigated the possible innovations implemented, treated from an institutional perspective of change in the work processes in university extension, whether in the administrative work of Proex staff or in the work of the teams that carried out the extension activities. Such snapshot is provided because university extension is an area where the university and social needs walk hand in hand being greatly affected by the pandemic. In methodological terms, this is an exploratory study using a qualitative, multi-methodological approach, through a case study, bibliographical research, documentary analysis, interviews, and participant observation. The participants chosen for this study were managers and technical-administrative staff from the Pro-Rectory of Extension and coordinators of extension activities. We interviewed four managers and fourteen technical-administrative staff from Proex/UFMG, three coordinators of UFMG extension activities and one occupational safety technician from the Department of Workers' Health Care (DAST/UFMG). Positive impacts include the reduction in daily commuting time, which has allowed civil servants to devote more time to their families, study, leisure and personal care, which has made many of them feel more motivated to carry out their work at the institution, the reduction in costs for the institution and greater autonomy and flexibility in the way workers carry out their activities. The content analysis of the materials collected, especially from the interviews, indicated the negative impact of teleworking, mainly in terms of the lack of socialization caused by carrying out activities away from the institution's premises. Problems related to physical health and ergonomics in teleworking were also highlighted. In addition, the innovative remote provision of outreach activities favored the participation and access of individuals from different parts of the country and abroad, resulting in greater dissemination and reach of UFMG's outreach activities, as well as the non-interruption of services provided by the university during the two peak years of the pandemic. The innovative way in which the work was carried out was through the use of tools based on information alongside communication technologies and remote team management. Some of the contributions of the results of this study are the need to improve UFMG teleworking policy, especially with regard to monitoring the health of civil servants, information security responsibilities and adapting institutional communication processes to teleworking.